Kitap İncelemesi: Dünyayı Değiştirmek İsteyenler Ulusu Nasıl Tasvir Ettiler? - Elçin Aktoprak (Alternatif Politika)
Nationalism is not only a feeling, but an identity, not just a form of movement, but a process that does not deny and cover all of this, and this process has been in a close relationship with capitalism since the 18th century. Since the date it has emerged, different elements of nationalist ideology have been instrumentalized and instrumentalized in different forms by nationalism at different times, as they are instrumentalized in different forms at different times in the capitalist economy. In the nationalist literature, especially in the framework of modern nationalism, the relation between nationalism and capitalism is an unobservable situation; Being a Marxist, many writers, especially Gellner, have established a relationship between the mode of production and nationalism, and have particularly emphasized the role of the bourgeoisie, and, more generally, the middle classes in nationalist movements. Nevertheless, Marxism is often criticized by Marxists themselves for not comprehensively addressing nationalism. These criticisms are the result of the fact that the emergence of the nation in Marxist studies is addressed only on the national market and that nationalism is presented as a certain stage of history, and that the historical socio-economic dynamics are overlooked.